Development Of Pugo Learning Media To Improve Early Childhood Cognitive Skills In Geometry Concepts - Nuryani Putri; Nita Priyanti; Chandra Apriyansyah (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aimed to develop PUGO learning media that is feasible and effective in improving early childhood cognitive abilities in understanding geometric concepts. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 57 children aged 4–6 years at TK Kemala Bhayangkari 11, Purwakarta Regency, divided into three groups: Group A with 17 children aged 4–5 years, Group B1 with 20 children aged 5–6 years, and Group B2 with 20 children aged 5–6 years. The research instruments included expert validation sheets and observation sheets measuring children's geometric cognitive abilities, covering four indicators: recognizing geometric shapes, naming geometric shapes, grouping geometric shapes, and arranging geometric shapes into patterns. The results showed that the PUGO media was highly feasible, with a validation score of 96.7% from three experts. Theoretical feasibility was supported by Piaget’s cognitive development theory, constructivist learning theory, play-based learning theory, multiple intelligences theory, and van Hiele’s geometric thinking theory. The media proved highly effective, increasing children's cognitive performance from 47.0% to 79.0%, representing a 68.1% improvement, with a gain score of 0.60 (moderate to high category). After implementation, 92% of children reached the “Developing as Expected” level or higher, indicating that PUGO media effectively supports early childhood understanding of geometric concepts through concrete and playful learning experiences.